Financiación sanitaria, pagos de bolsillo y desigualdad del ingreso: evidencia de un panel internacional (2000–2020) - Karen Andrea Balladares Ponguillo; José Roberto Morales Vergara; Juan Evangelista Trinidad Segovia; Danny Xavier Arevalo Avecillas (Revista Galega de Economía, 2026)
This study examines the relationship between health financing mechanisms and income inequality using an international panel of 135 countries over the period 2000–2020. From a macro-comparative perspective, the analysis focuses on total health expenditure as a percentage of GDP and the share of out-of-pocket payments within total health spending, while controlling for key macroeconomic and social variables including GDP per capita, unemployment, inflation, education, and health outcomes. Methodologically, the study estimates a country fixed-effects model to capture contemporaneous within-country associations and, as a robustness exercise, a dynamic panel specification using the Arellano–Bond difference GMM estimator to account for the temporal persistence of income inequality. The static results suggest that higher overall health expenditure is associated with moderate reductions in income inequality, whereas a greater reliance on out-of-pocket payments is linked to increases in the Gini coefficient, consistent with their regressive nature. However, once dynamic persistence is incorporated, these effects lose statistical significance, while income inequality exhibits strong structural inertia. Unemployment and infant mortality emerge as relevant determinants of inequality across specifications. Overall, the findings indicate that health financing structures matter for distributive outcomes, but their effects are neither immediate nor independent of entrenched inequality trajectories. Health reforms should therefore be conceived as part of broader, long-term redistributive strategies integrated with labor market and fiscal policies.